Examining the relationships between quality assurance, training need and choice of study destination: a study of Nigerian students in UUM - Usman, Abbo; Romle, Abd Rahim; Qader, Mohammed Mustafa (EconJournals, 2015)
Several studies identified quality of education as a major criteria influencing international student’s choice of study destination. But only recently has it seems to have gain a huge momentum by emerging as a theme which involves empirical studies.However, despite such momentum previous studies do not provide sufficient evidence linking quality assurance and international student’s choice of study destination.This paper therefore presents a study of international student’s perception of higher education quality assurance practices, as well as how it affects their choice of study destination.The paper tries to examine how training needs play a role in influencing such choice also. The paper through descriptive analysis identified six dimensions of quality assurance in education: “Tangibles” “competence” “attitude contends;” “delivery;” and “reliability” as well as three dimensions of training needs such “occupational” “organizational” and “individual” needs. Hence it present the inter-relationship between quality assurance, training needs and choice of study destination using the above nine dimension; it concludes with Implications and recommendations to stimulate further studies on study destination choice by the international students from other countries especially from the Arabian and the middle-east.